2019
DOI: 10.3390/geosciences9070290
|View full text |Cite
|
Sign up to set email alerts
|

NN-Based Prediction of Sentinel-1 SAR Image Filtering Efficiency

Abstract: Images acquired by synthetic aperture radars are degraded by speckle that prevents efficient extraction of useful information from radar remote sensing data. Filtering or despeckling is a tool often used to improve image quality. However, depending upon image and noise properties, the quality of improvement can vary. Besides, a quality can be characterized by different criteria or metrics, where visual quality metrics can be of value. For the case study of discrete cosine transform (DCT)based filtering, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Obviously, this should be metrics applicable for grayscale images and possessing good adequateness with respect to peculiarities of human vision system (HVS). In this sense, we can further employ earlier experience [22,26] concerning visual quality metrics [27][28][29][30] and their use in SAR image processing [26].…”
Section: Image/noise Modelmentioning
confidence: 97%
See 3 more Smart Citations
“…Obviously, this should be metrics applicable for grayscale images and possessing good adequateness with respect to peculiarities of human vision system (HVS). In this sense, we can further employ earlier experience [22,26] concerning visual quality metrics [27][28][29][30] and their use in SAR image processing [26].…”
Section: Image/noise Modelmentioning
confidence: 97%
“…Then, to get quantitative evaluation of speckle suppression efficiency, we need means for modelling speckle with the determined properties. Methods to do this have been earlier described in our papers [23,26]. In Fig.…”
Section: Image/noise Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper we consider the Frost filter [7] since it is still widely used in various toolboxes like SNAP [11]. Our previous studies have shown that it is possible to predict despeckling efficiency beforehand with high accuracy for several filters [12]. We have already demonstrated how to select the window size for the well-known local statistics Lee filter based on despeckling efficiency prediction [10].…”
Section: Introductionmentioning
confidence: 99%